2014
DOI: 10.5897/jmpr12.976
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the antimicrobial activity of aqueous and ethanolic extracts of Piper guineense leaves

Abstract: The antimicrobial activity of aqueous and ethanolic extracts of leaves of Piper guineense was determined on some bacteria and fungi, namely, Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Bacillus subtilis, Candida albicans and Saccharomyces cerevisiae, using agar well diffusion method and minimum inhibitory concentration (MIC). The ethanolic extract was found to show more activity than the aqueous extract on all the isolates. The diameter of zones of inhibition for the ethanolic extract rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…This finding is not in agreement with Ebana et al [12] who reported the inability of ethanolic extract of P. guineense to inhibit P. aeruginosa, while aqueous extract did. Aboaba et al [15] and Anyanwu and Nwosu [11] however, reported the inhibition of P. aeruginosa by both the aqueous and ethanol extract of P. guineense, with the ethanol zones of inhibition comparable to the finding of this study. The finding of this study is in agreement with reports by Osuala and Anyadoh [34] that methanolic extracts of P. guineense exhibited much more antibacterial activity against P. aeruginosa than the ethanolic extracts, recommending that methanol be used in preference to ethanol in extracting active ingredients from plants.…”
Section: Antibacterial Activity Of P Guineensesupporting
confidence: 75%
“…This finding is not in agreement with Ebana et al [12] who reported the inability of ethanolic extract of P. guineense to inhibit P. aeruginosa, while aqueous extract did. Aboaba et al [15] and Anyanwu and Nwosu [11] however, reported the inhibition of P. aeruginosa by both the aqueous and ethanol extract of P. guineense, with the ethanol zones of inhibition comparable to the finding of this study. The finding of this study is in agreement with reports by Osuala and Anyadoh [34] that methanolic extracts of P. guineense exhibited much more antibacterial activity against P. aeruginosa than the ethanolic extracts, recommending that methanol be used in preference to ethanol in extracting active ingredients from plants.…”
Section: Antibacterial Activity Of P Guineensesupporting
confidence: 75%
“…Hazard index was calculated as the sum of hazard quotients (HQs) [13][14][15][16]. Since different pollutants can cause similar adverse health effects, it is often appropriate to combine HQs associated with different substances [17][18][19][20][21].…”
Section: Calculation Of Hazard Indexmentioning
confidence: 99%
“…Compounds 20 and 26 showed significant activities against B. subtilis and C. albicans, MIC = 0.313-1.25 lg/mL, where the activity of pyrazolinones 20 was better than that of isoxazolinone 26. Antifungal activities were also shown by compounds 13,14,17,19,21,23, and 25, with 8-11 mm inhibition zones.…”
Section: Antimicrobial Screeningmentioning
confidence: 99%
“…Agar well diffusion method was used for initial screening at concentrations of 100 lg/mL. 23,24 Minimum inhibitory concentrations (MIC) were determined for samples which showed activity. 23,24 Gram-positive organisms (Staphylococcus aureus ATCC 25923, Bacillus subtilis NCIB 3610), Gram-negative organisms (Pseudomonas aeruginosa NCIMB 8295, Escherichia coli ATCC 8739) and a fungal yeast Candida albicans were obtained and confirmed at the Microbiology Laboratory, Department of Biological Sciences, University of Botswana.…”
Section: Antimicrobial Screeningmentioning
confidence: 99%